Students’ Perceptions of Project Based Learning in Democratic Voice : Interdisciplinary Approach in Citizenship Education and Islamic Religious Education - Vachruddin, Vrisko Putra; Nashrullah, Nashrullah; Rusydiyah, Evi Fatimatur (FKIP Universitas Lampung, 2024)
Students’ Perceptions of Project Based Learning in Democratic Voice: Interdisciplinary Approarch in Citizenship Education and Islamic Religious Education.[vp1] Objectives: Through the theme of voice of democracy, the school designs project-based learning through an interdisciplinary approach to the subjects of citizenship education and Islamic religious education. This study aims to analyze students' perceptions of the project's learning based on perceptions of interest, motive, responsibility and objectivity. Methods: This research is a type of survey research with data collection through questionnaires, in-depth interviews and observations. The questionnaire was compiled based on a five-point Likert scale which was distributed randomly to 147 respondents in the form of students. Data analysis on the questionnaire used SEM (structural equality modeling) analysis with the SMART PLS 4.0 program. Findings: The results of this study are 1). The perception of interest negatively affects the objectivity of the election of the student council president. Awareness and interest of students need to be increased through learning and programs that increase student motivation. 2). The perception of motives and responsibilities positively affects objectivity and interest. Conclusion: Personal and group interests must be avoided in order to provide a sense of responsibility for students towards the objectivity of electing the student council chairman. Keywords: students perceptions, democratic voice, interdisiplinary approarch, citizenship education.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024106